ANALISIS KUALITAS BUTIR SOAL UJIAN AKHIR SEMESTER GENAP PADA MATA PELAJARAN GEOGRAFI KELAS X IIS TAHUN AJARAN 2018/2019 DI SMA PERTIWI 1 PADANG - Melly Rahma Sari; surtani surtani (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This study aims to determine the quality of the Even Semester Final Examination items in terms of Validity, Reliability, Difficulty Level, Distinguishing Power and the Effectiveness of Deceiters in Class X IIS Geography Subjects in 2018/2019 Academic Year 1 of SMA Pertiwi Padang. This type of research is quantitative descriptive. The population of this study was all students of class X IIS at Pertiwi 1 Padang High School, totaling 86 people. Sampling using the Slovin formula obtained by 42 respondents. Data collection techniques in this study are documentation by collecting data in the form of exam questions, student answer sheets. This data analysis technique was carried out using ANATES multiple choice software rocks Ver 4. 0. 9. The results of research conducted showed that (1) (1) in terms of validity, item A and B items were declared valid at 36.7% and invalid 63.7%. (2) Reliability of Item A package shows the value of 0.85 is categorized high. In Package B showing a value of -2, 41 are categorized as very low. (3) The difficulty level of Package A items is 10% easy, 50%, and 40% difficult. In Package B that is 16, 5% easy, 56.6% moderate, and 26.7% difficult. (4) Distinguishing Power of Package A items, namely 6.7% is very good, 30% is good, 23.3% is sufficient, and 40% is bad. In Package B, 3.3% is very good, 13.3% is good, 23.3% is sufficient, and 60% is bad. (5) The effectiveness of Deception items on Package A is 76.7% very good, 13.3% is good, 10% is good enough and 0% is not good enough. In Package B, 36.7% is very good, 36.7% is good, 23.3% is good enough and 3.3% is not good.